What do we know about the future of aquatic foods in global agrifood systems? - Chan, Chin Yee; Tran, Nhuong; Hoong, Yan; Sulser, Timothy B.; Aung, Yee Mon (International Food Policy Research Institute, 2025)
Demand for aquatic foods has increased rapidly due to population growth, rising incomes, and enhanced appreciation for the health benefits of fish. The rapid growth of aquaculture in the past two decades has been the key contributor to meeting the increasing demand for aquatic foods.